- Serum Cytokines as Potential Biomarkers for Diagnosis and Monitoring of Sleep Disorders: A Cross-Sectional and Longitudinal Study: Serum levels of IL-6, TNF-α, IL-1β, IL-10, and CRP - Yao, Yongliang; Pan, Yifan; Yan, Lei; Zheng, Chaoan (Journal of Medical Biochemistry, 2026)
Background: Sleep disorders, particularly Obstructive Sleep Apnea (OSA) and Insomnia Disorder (ID), are associated with systemic inflammation. However, the diagnostic and monitoring utility of specific cytokine profiles remains unclear.Objective: To identify distinct serum cytokine signatures in OSA and ID compared to healthy controls (HC) at baseline and to evaluate longitudinal changes in these biomarkers following standard treatment.Methods: In this pilot study, 75 cases (25 OSA, 25 ID, 25 HC) were enrolled. Serum levels of IL-6, TNF-α, IL-1β, IL-10, and CRP were measured at baseline using multiplex immunoassay. All patients underwent polysomnography and clinical assessment. The OSA and ID cohorts were re-evaluated after 3 months of treatment (CPAP for OSA, CBT-I for ID) with repeat cytokine analysis.Results: At baseline, the OSA group showed significantly elevated levels of IL-6 (p
Keywords: Biomarkers, Inflammation, Cytokines, Obstructive Sleep Apnea, Insomnia, CPAP, Cognitive Behavioral Therapy.